Education as a subversive activity: a proposal. Issue 9 (3rd November 2014) - Richards, Larry
Abstract : Purpose: – The purpose of this paper is to present a case for a change of educational system, rather than a change in the current system. A rudimentary framework for an alternative educational system is proposed. Design/methodology/approach: – Cybernetic and educational literature supports an alternative approach to education. Design principles are identified for an alternative system. Findings: – For the desirable integration of curricular and pedagogical principles to be realized in an educational system, a non-hierarchical organizational structure is required. The icosahedral structure that embeds Stafford Beer's syntegration process provides such a default structure. Such a structure would be subversive in the current society. Social implications: – The implementation of the proposed system of schools could transform society by offering an alternative way of thinking about the structure of organizations like schools, as well as political and economic organizations. In so doing, fully participative democratic processes could be realized and sustained. Originality/value: – The use of the icosahedral structure as a framework for creating a system of schools world-wide is new and has value for anyone contemplating alternative educational systems.